BRIDGING THE GAP: MALE AGING, CONSUMER BEHAVIOR, AND STRATEGIC MARKETING OPPORTUNITIES - Shen, Tsung-Nan (PEOPLE: International Journal of Social Sciences, 2025)
This study explores the psychological perceptions of aging traits in men and their impact on consumer behavior and marketing strategies, addressing a gap in prior research predominantly focused on women. This research adopts a qualitative approach through one-on-one in-depth interviews, involving 30 participants from diverse age groups. Findings indicate that key aging traits in men include gray hair, baldness, wrinkles and spots, changes in body shape (e.g., beer belly), psychological and behavioral aging, and odor associated with aging. These traits not only signify physical and behavioral aging but also influence men’s self-confidence and perceptions of their social roles. Unlike women, men’s anxiety about aging is more centered on fears of declining social value and health, profoundly affecting their professional capabilities and image management needs. This research bridges the gap in understanding men’s aging psychology and consumer behavior, offering theoretical and practical insights for developing precise marketing strategies targeting male audiences. It also promotes dual benefits of commercial and social value by aligning with gender equality and aesthetic diversity, providing a reference for future cross-cultural studies on men’s aging.